THE ROLE OF METONYMY IN TONGUE TWISTERS (International Conference on Medical Science, Medicine and Public Health, 2025)
Tongue twisters, known for their playful use of phonetics, are often analyzed for their linguistic properties. This article explores the concept of metonymization in tongue twisters within the English language. Metonymy, as a cognitive and linguistic process, involves the substitution of one term for another based on a related association. In the case of tongue twisters, metonymization manifests through the association between sounds, syllables, and words. This article examines how metonymy operates within tongue twisters, focusing on how sound patterns evoke meanings and cognitive shifts. The study highlights how the interplay of phonetic resemblance and cognitive association results in a unique linguistic experience in tongue twisters. Key examples from both classic and modern tongue twisters will be analyzed to illustrate this phenomenon.